COMPARATIVE EVALUATION OF THE EFFECTIVENESS OF CARBAMAZEPINE AND GABAPENTIN IN THE MANAGEMENT OF TRIGEMINAL NEURALGIA - Priya Devi; Azan Hassan; Jaya Kumari; Sameer Ahmed; Muhammad Tahir; Sandhiya kumari; Kiran Devi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Trigeminal neuralgia (TN) is a chronic pain condition characterized by severe, recurrent facial pain. The management of TN primarily involves pharmacotherapy, with Carbamazepine and Gabapentin being commonly prescribed anticonvulsants. Objectives: This study aimed to compare the efficacy and safety of Carbamazepine and Gabapentin in the treatment of TN. Materials & Methods: A prospective, randomized, open-label trial was conducted involving 120 patients diagnosed with TN at Department of Pharmacology and Therapeutic at Islam Medical and Dental College, Sialkot from Jan 2021 to June 2022. Patients were randomly assigned to receive either Carbamazepine (n=60) or Gabapentin (n=60). The primary outcome was pain reduction, measured by the Visual Analog Scale (VAS). Secondary outcomes included the frequency of pain episodes, quality of life (assessed using the SF-36 questionnaire), and the incidence of adverse effects. Patients were followed for 12 weeks, with assessments at baseline, 4, 8, and 12 weeks. Results: Both treatment groups showed significant reductions in pain severity and improvements in quality of life. The mean VAS score decreased from 8.6 ± 1.2 to 3.1 ± 1.6 in the Carbamazepine group and from 8.4 ± 1.3 to 3.7 ± 1.8 in the Gabapentin group. The reduction in pain episodes was more pronounced in the Carbamazepine group (15.8 ± 5.4 to 5.2 ± 3.1) compared to the Gabapentin group (16.1 ± 5.2 to 6.4 ± 3.5) (p=0.04). SF-36 scores improved significantly in both groups, with no significant difference between them (p=0.12). However, the incidence of adverse effects was higher in the Carbamazepine group (63%) compared to the Gabapentin group (42%) (p=0.01). Conclusion: Both Carbamazepine and Gabapentin are effective in managing trigeminal neuralgia, with Carbamazepine providing slightly superior pain relief. However, Gabapentin was better tolerated, with fewer adverse effects.